2012
DOI: 10.1021/ac301814e
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Strategies for SERS Analysis of Indigo and Prussian Blue in Aged Painted Surfaces

Abstract: Surface-enhanced Raman scattering (SERS) spectroscopy is increasingly applied to the identification of organic colorants in cultural heritage objects because vibrational fingerprints can be measured from microscopic samples. However, the development of SERS into a reliable, broad-spectrum method for art analysis requires the study of a wide variety of organic and inorganic colorants as well as colorant mixtures in paint. Here, we demonstrate reliable protocols for SERS-based identification of insoluble indigo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 41 publications
(105 reference statements)
3
51
0
Order By: Relevance
“…Indigo dye is usually easily detectable in dispersive conditions by means of Raman spectroscopy by adopting for analyses laser lines at high wavelength [6], which are sufficient to quench the fluorescence background and to detect the molecule. Unfortunately, the recognition of this compound may be quite difficult when analyzing ancient artworks, as for instance textiles, where the dye is present at very low concentrations, or paint layers, where the colorant is generally incorporated within complex pigment mixtures [7][8][9]. Moreover, degradation processes or bad state of conservation of the art object may further affect the analyses of the blue dye.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indigo dye is usually easily detectable in dispersive conditions by means of Raman spectroscopy by adopting for analyses laser lines at high wavelength [6], which are sufficient to quench the fluorescence background and to detect the molecule. Unfortunately, the recognition of this compound may be quite difficult when analyzing ancient artworks, as for instance textiles, where the dye is present at very low concentrations, or paint layers, where the colorant is generally incorporated within complex pigment mixtures [7][8][9]. Moreover, degradation processes or bad state of conservation of the art object may further affect the analyses of the blue dye.…”
Section: Introductionmentioning
confidence: 99%
“…The first semiquantitative study of indigo using SERS/SERRS was reported by Shadi et al [27], who investigated methanolic solutions of the blue dye combined with silver colloidal dispersions aggregated by means of HCl. In the specific case of cultural heritage applications, SERS-based detection of indigo has been reported for the analysis of paintings [28], textiles [8,29,30], and archaeological objects [31]. Recently, a pioneering application of tip enhanced Raman spectroscopy (TERS) has also been presented for the in situ identification of indigo in paper artworks [32].…”
Section: Introductionmentioning
confidence: 99%
“…Beside successfully detecting red lakes in combination in a few cases, SERS was used by Oakley et al (2012) upon treatment with sulfuric acid to probe mixtures of blue inorganic pigments and organic colorants, i.e. Prussian blue and indigo, in a single sample from the early 18th-century oil painting Portrait of Evelyn Byrd (1725-26).…”
Section: Paintingsmentioning
confidence: 99%
“…Articles about the detection of flavonoids (Jurasekova et al 2006(Jurasekova et al , 2008(Jurasekova et al , 2012Wang et al 2007;Teslova et al 2007;Cañamares et al 2009;Corredor et al 2009;Mayhew et al 2013), indigoids (Bruni et al 2010;Oakley et al 2012), and dyes belonging to other molecular classes Cañamares et al 2008aCañamares et al , b, 2010Cañamares et al , 2014Fig. 1 Schematic of the surface-enhanced Raman scattering process.…”
Section: Introductionmentioning
confidence: 99%
“…Holding the wish for SERS application in food and environmental monitoring [26][27][28][29] and SERS-based diagnose [30,31], it is of the essence for exploring the appropriate synthesis methods to develop the high performance nanostructures for improving the sensitivity and reproducibility of SERS [32]. In amongst, bimetallic silver-coated gold colloids (Au@Ag NPs) were prepared for identification of toxic food additives.…”
Section: Introductionmentioning
confidence: 99%